UNILATERAL CANCELLATION OF AGREEMENT IN A BUSINESS CONTRACT - Irenda Destian; Miftahul Haq; Yelia Nathassa Winstar (JILPR Journal Indonesia Law and Policy Review, 2026)
The purpose of this research is to analyze unilateral cancellation of agreements in business contracts and to analyze the legal consequences of unilateral cancellation of agreements in business contracts. The method used is normative legal research. Based on the research results, it is known that unilateral cancellation of agreements in business contracts is, in principle, not permitted if it is carried out without the consent of the other party or without a valid legal basis. Based on Article 1338 of the Civil Code, every legally made agreement binds the parties as law. Therefore, contract cancellation must be based on the agreement of the parties, the existence of a breach of contract, force majeure, or a court decision. Supreme Court Jurisprudence Number 4/Yur/Pdt/2018, derived from Supreme Court Decision Number 1051 K/Pdt/2014, also confirms that unilaterally canceling an agreement without legal basis is unlawful. The legal consequences of unilateral cancellation of an agreement in a business contract are that the party canceling the agreement can be declared in default and obligated to pay compensation in accordance with the provisions of the Civil Code. Furthermore, the injured party has the right to file a lawsuit to demand cancellation of the contract, fulfillment of performance, or compensation. Unilateral cancellation also reduces legal certainty and trust in business relationships, so contract implementation must always be based on the principles of good faith, legal certainty, and balance between the parties.